Phytoplankton Functional Groups Variation and Influencing Factors in a Shallow Temperate Lake: Tian et al. (1st June 2018) - Tian, Chang; Hao, Daping; Pei, Haiyan; Doblin, Martina A.; Ren, Ying; Wei, Jielin; Feng, Yawei
ABSTRACT: : The present study was carried out in Luoma Lake, a shallow lake in temperate eastern China. Based on a two‐year study, the dynamics of phytoplankton functional groups and influencing factors were analyzed. A total of 178 taxa were identified and sorted into 20 codons, according to the phytoplankton functional group classification. In order to find the environmental factors driving phytoplankton variations, fifteen groups were analyzed in detail using redundancy analysis. GroupsP ( Fragilaria crotonensis ), X2 ( Chlamydomonas globosa, C. microsphaera and Chroomonas acuta ), andMP ( Navicula rotaeana ) were dominant during low temperature periods, whereas groupsX2, S1 ( Pseudanabaena limnetica ), andW1 ( Euglena sp .) were dominant during high temperature periods. Water temperature, total phosphorus, and ammonium were the significant driving factors explaining phytoplankton succession. Furthermore, total phosphorus and ammonium could be broadly used in risk management for potential algal blooms in Luoma Lake.